2016
DOI: 10.5958/0974-0279.2016.00033.1
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Pattern and Nutritional Intake of Pulses by Segregated Income Groups in India

Abstract: The changes in consumption pattern of different pulses and consequently in nutrient intake arising due to price and income changes at household level have been analysed using the consumer expenditure survey data for the year 2011-12. The share of expenditure on red gram in the total food expenditure has been found higher as compared to other pulses, irrespective of the income levels of households. The consumption of most of pulses has been observed more responsive to changes in the income of all the income hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In separate models, purchases of milk and pulses increased across India with an INR 500 increase in income. Earlier studies from India have shown that the consumption of pulses is responsive to change in income of households 35. Income doubling has been shown to increase the consumption of non-staple foods, including non-vegetarian foods by about 110% 36.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In separate models, purchases of milk and pulses increased across India with an INR 500 increase in income. Earlier studies from India have shown that the consumption of pulses is responsive to change in income of households 35. Income doubling has been shown to increase the consumption of non-staple foods, including non-vegetarian foods by about 110% 36.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this correlation could vary geographically, thus introducing additional variability in the estimates of stunting reduction. How well a household wealth index serves as a proxy for income is not well understood,35 and there are concerns that, given alternative demands for cash expenditure such as housing and education, cash transfers may not be spent on nutrient-rich foods or on supporting more healthy diets.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, India is the largest producer and consumer of pulses in the world, but consumption exceeds production and is therefore supported by imports. In 2014–15, India produced 17.4 million tonnes of pulses and consumed 22.7 million tonnes, with imports amounting to 4.6 million tonnes ( Umanath et al, 2016 ). The gap between demand and domestic supply of pulses is expected to widen over time.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have proved that the improvement in agricultural productivity has positive effect on reduction in rural poverty and economic disadvantage of a region (Chand and Srivastava, 2016). Studies have also established that increase in the per capita income of the households increases the intake of all nutrients by the households (Umanath et al,2015). Thus improvement in agricultural productivity under mountain specificities of Garo Hills should be taken on priority basis.…”
Section: Malnutrition Among Children Of 6-59 Monthsmentioning
confidence: 99%